Dispersion of Boron Nitride Powders in Aqueous Suspensions with Cellulose. Issue 2 (8th January 2014) - Bouville, Florian; Deville, Sylvain; Gauckler, L.
<x xml:space="preserve">Abstract</x> The dispersion of nitride and carbide ceramic particles in water is difficult, due to the absence of hydroxyl groups on their surface. Boron nitride (BN) is not an exception and despite its numerous applications, no effective dispersant has been identified so far. We demonstrate here the dispersion properties of two cellulose derivatives for hexagonal BN powders, hydroxyl ethyl cellulose and methyl cellulose. The effect of particle size and cellulose concentration was investigated. The adsorption of cellulose onto the surface of the BN particles was confirmed by isotherm adsorption. Zeta potential measurements show a charge screening effect of the cellulose The suspensions obtained were highly loaded and stable versus pH, and thus could lead to homogeneous codispersion of BN particles and sintering additives.